(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This research was conducted to describe the performance of Meyerga village chief from West Moksona District, Teluk Bintuni Regency. The results of this study are expected to provide benefits for the development of public administration science, especially about performance, and practically become an evaluation for Meyerga village chief from West Moksona District, Teluk Bintuni Regency to improve his/her performance. This research uses qualitative design focusing on work quality, quantity and timeliness. Data were collected through interviews with informants from the West Moksona District government elements, the government and villagers of Meyerga village, followed by our own observation and documentation studies. Data analysis were done through data reduction, data display, data conclussions drawing/verification. The result shows that the performance of the village chief in the development program is going well because the development implemented until now has been running as planned. The performance in running the government has not been good because of the lack of knowledge and skills possessed by the village chief and other village officials in understanding the rules and work procedures of governance, the mastery of village government administration included. The performance of the village chief in the implementation of community development is already good due to his presence as a respected community leader and also the support of community leaders and religious leaders for the village chief in conducting community development. The performance of the village chief in the community empowerment program has not been good due to lack of clarity of village government programs to improve the community’s capacity in terms of education, community development and to young generation and women. This research concludes that the performances of Meyerga village chief of West Moksona District of Teluk Bintuni Regency, West Papua Province based on work quality, work quantity and utilization of working time has been well done in the field of development and community development and has not run well in the field of government, and community empowerment. It is therefore advisable to undertake training for making village government work plans, complementing work facilities, continuously strengthening relationships with religious leaders and community leaders. Adapting the work programs in the field of community empowerment focused on youth empowerment, community development and women is needed. Keywords: Performance, Village Chief